Development of Hexapod Fire Extinguisher Robot Navigation System Using LIDAR (Light Detection and Range) - Sutoyo, Edi; Sutisna, Setya Permana; Siregar, Tika Hafzara; Komara, Indra (Ibn Khaldun International Journal of Applied Sciences and Sustainability, 2023)
Design of a navigation system on a hexapod robot for fire extinguisher using LIDAR (Light Detection And Range) are introduced in this paper. the LIDAR sensor used in this study is the Tfmini Lidar which functions as a detecting obstacle object and equipped with the 5 channel flame array sensor used to detect the presence of a fire source. The navigation system was designed to be able to find out fire existence. the robot has been carried out several tests to compare the speed performance of the navigation system with remote control (manually controlled) and autonomous control in fire source room. The results showed the Tfmini LIDAR reading test can read a distance of 0.15 -12 meters with average error of 0.51%. Tfmini LIDAR was not affected by light intensity but still cannot detect clear objects such as acrylic and mineral water bottles. The travel time obtained by the system with autonomous control in navigating to the room source of fire was 50.972 seconds and manually control was 40.07 seconds. Based on the results, the navigation system using LIDAR has been successfully designed and can be implemented for a hexapod fire extinguisher robot.